2015
DOI: 10.3109/00207454.2015.1005291
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine preconditioning attenuates global cerebral ischemic injury following asphyxial cardiac arrest

Abstract: Dexmedetomidine preconditioning protected against cerebral ischemic injury and was associated with upregulation of HIF-1α and VEGF expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
0
14
0
2
Order By: Relevance
“…In contrast, there was no benefit from an 8 h pre-ischemic exposure to either halothane or propofol. That a brief anesthetic exposure improves the outcome of a cerebral ischemic insult has been extended to isoflurane [131], sevoflurane [132], dexmedetomidine [133] and chloral hydrate [134], including long term (2-4 weeks) outcome [135, 136]. In contrast, alpha-chloralose may be devoid of this property [65], and ketamine may indeed block ischemic preconditioning mediated by activation of the NMDA receptor [137].…”
Section: Anesthetic Preconditioningmentioning
confidence: 99%
“…In contrast, there was no benefit from an 8 h pre-ischemic exposure to either halothane or propofol. That a brief anesthetic exposure improves the outcome of a cerebral ischemic insult has been extended to isoflurane [131], sevoflurane [132], dexmedetomidine [133] and chloral hydrate [134], including long term (2-4 weeks) outcome [135, 136]. In contrast, alpha-chloralose may be devoid of this property [65], and ketamine may indeed block ischemic preconditioning mediated by activation of the NMDA receptor [137].…”
Section: Anesthetic Preconditioningmentioning
confidence: 99%
“…It is well known that CI triggers a complex cascade of metabolic alterations involved in multiple biological pathways such as oxidative stress [1, 2], inflammation [3], neuronal damage [4], and hypoxia-inducible factor [5]. The biomarkers connect directly or indirectly with each other to form a complex network in the diverse pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated subunit HIF-1α in the cellular nucleus and cytoplasm modulates the expression of several target genes that involve in neuroprotection, erythropoiesis, and apoptosis modulation [11,12]. Additionally, inadequate oxygen supply appears in the brain regions during global ischemia, which is associated with ischemiaevoked pathophysiologic changes [13,14]. Recent studies have demonstrated that HIF-1α is expressed in the brain tissues including hippocampus, indicating that HIF-1α is engaged in hippocampal apoptosis after induction of global ischemia [6,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, inadequate oxygen supply appears in the brain regions during global ischemia, which is associated with ischemiaevoked pathophysiologic changes [13,14]. Recent studies have demonstrated that HIF-1α is expressed in the brain tissues including hippocampus, indicating that HIF-1α is engaged in hippocampal apoptosis after induction of global ischemia [6,[13][14][15]. Using a rat model of asphyxial cardiac arrest (CA), our recent study has further demonstrated that HIF-1α is increased in the hippocampus of rats with CA [16].…”
Section: Introductionmentioning
confidence: 99%